BACE1 inhibitory activity of fungal endophytic extracts from Malaysian medicinal plants - Cole Anthony LJ; Majeed Abu; Lim Siong; James Richard; Harun Azzeme; Ramasamy Kalavathy (BMC, 2011)
Abstract Background BACE1 was found to be the major β-secretase in neurons and its appearance and activity were found to be elevated in the brains of AD patients. Fungal endophytic extracts for BACE1 inhibitory activity and cytotoxicity against PC-12 (a rat pheochromocytoma with neuronal properties) and WRL68 (a non-tumorigenic human hepatic) were investigated. Methods Endophytes were isolated from plants collected from Kuala Pilah, Negeri Sembilan and the National Park, Pahang and the extracts were tested for BACE1 inhibition. For investigation of biological activity, the pure endophytic cultures were cultivated for 14 days on PDA plates at 28°C and underwent semipolar extraction with ethyl acetate. Results Of 212 endophytic extracts (1000 μg/ml), 29 exhibited more than 90% inhibition of BACE1 in the preliminary screening. Four extracts from isolates HAB16R13, HAB16R14, HAB16R18 and HAB8R24 identified as Cytospora rhizophorae were the most active with IC50(BACE1) values of less than 3.0 μg/ml. The most active extract HAB16R13 was shown to non-competitively inhibit BACE1 with Ki value of 10.0 μg/ml. HAB16R13 was considered non-potent against PC-12 and WRL68 (IC50(CT) of 60.0 and 40.0 μg/ml, respectively). Conclusions This first report on endophytic fungal extract with good BACE1 inhibitory activity demonstrates that more extensive study is required to uncover the potential of endophytes.